Effects of coupled application of magnetoelectric activated water and amendments on photosynthetic physiological characteristics and yield of maize in arid regions - Lei, Qingyuan; Tao, Wanghai; Yang, Fan; Liu, Jianqi; Xi, Zixuan; Wang, Quanjiu; Deng, Mingjiang (Frontiers in Plant Science, 2025)
Seeking effective improvement agent control measures to enhance the photosynthetic physiological traits and yield levels of spring maize is crucial for efficient green agriculture in arid regions. Therefore, this study was conducted to clarify the effects of coupling improvement agents under magnetoelectric activated water irrigation conditions on the photosynthetic physiological traits, grain nutrients, and yield of spring maize in the arid region of northwest China. Field experiments were set up with three concentrations of growth regulators: 400 times (G1), 500 times (G2), and 600 times (G3), and three amounts of Bacillus subtilis: 15 kg/ha (R1), 45 kg/ha (R2), and 75 kg/ha (R3), along with a control group CK, making a total of 10 treatments applied in the field experiment. The results indicate that under magnetoelectric activated water irrigation, coupling improvement agents significantly enhance the photosynthetic traits, grain nutrients, and yield of spring maize in arid areas. With the coupling of improvement agents, the rectangular hyperbola correction model showed a good fit for the light response curve (R2>0.992). Pnmax was significantly increased (7.37%~37.46%) and was highly correlated with yield (P<0.01). The entropy-weight TOPSIS comprehensive evaluation analysis found that the G2R2 treatment is the optimal improvement agent coupling measure for efficient production of spring maize in arid regions. This treatment yielded 12.68 t/ha and increased 100-kernel weight, grains per spike, and soluble sugar content by 21.3%, 8.22%, and 63.81%, respectively, representing the best balance of quality and high yield. The results of this study provide theoretical references and technical support for the high-quality and efficient production of spring maize in China’s arid regions.